Contaminación sonora por ruido vehìcular y sus efectos en la zona céntrica oriental regenerada de la ciudad de Loja. - Castro Herrera, David Andrès (2019)
The present research work consisted of knowing the levels of noise pollution generated by the automotive park, in the regenerated eastern central area of the city of Loja, where the sound pressure was analyzed, and the cause-effect relationship between noise levels and the appearance of psychosomatic disorders of those who work and reside in this sector. For this 107 measurement points were taken, which were located in the main and secondary streets taking in each place three repetitions, ten minutes in three different schedules (07h00- 09h00; 11h00-13h00; 17h00-19h00) and the number of vehicles traveling in this area was counted. With the data obtained, six noise maps were made using ArcGis 10.3 software where it was observed that the averages of the main streets in the three schedules were: 68.27dB; 68.71 dB; 69.36 dB and the averages of the secondary streets were: 65.23 dB; 65.97 dB; 65.48 dB respectively, exceeding the 65 dB allowed during the daytime according to the regulations. In addition, 117 surveys aimed at people who live and work in this part of the city were applied, to determine what are the effects and discomforts that they have suffered from the acoustic pressure, followed by this, we proceeded to develop an attenuation plan for noise in which there are programs focused on the reduction of noise pollution in the study area. The present study concluded that for the most part of the city, there is noise pollution especially in the main streets, in addition to one of the inconveniences that most affect people, is stress, due to the high noise levels. Keywords: Noise, automotive park, noise maps, decibels.